+0  
 
0
43
1
avatar

If a and b satisfy

 

2a/(a - 2b) - 6b/(a + 2b) = 3

 

a/(a - 2b) + 6b/(a + 2b) = -1

 

What is ab/(a^2 - 4b^2)?

 Mar 7, 2021
 #1
avatar+498 
-1

Start by simplifying the terms:

\(\frac{2a}{a-2b} - \frac{6b}{a+2b} = 3\)

\(\frac{(2a)(a+2b)-(6b)(a-2b)}{(a-2b)(a+2b)} = 3\)

\(\frac{2a^2 -2ab +12b^2}{(a-2b)(a+2b)} = 3\)

\(\frac{2a^2 -2ab +12b^2}{a^2-4b^2} = 3\)

 

\(\frac{a}{a-2b}+\frac{6b}{a+2b}=-1\)

\(\frac{(a)(a+2b)+(6b)(a-2b)}{(a-2b)(a+2b)}=-1\)

\(\frac{a^2+8ab-12b^2}{(a-2b)(a+2b)}=-1\)

\(\frac{a^2+8ab-12b^2}{a^2-4b^2}=-1\)

Can you take it from there? 

 Mar 7, 2021

40 Online Users

avatar
avatar
avatar
avatar